Intestinal Snakeskin Limits Microbial Dysbiosis during Aging and Promotes Longevity - Salazar, Anna M.; Resnik-Docampo, Martin; Ulgherait, Matthew; Clark, Rebecca I.; Shirasu-Hiza, Mimi; Jones, D. Leanne; Walker, David W. (iScience, 2018)
Intestinal barrier dysfunction is an evolutionarily conserved hallmark of aging, which has been linked to microbial dysbiosis, altered expression of occluding junction proteins, and impending mortality. However, the interplay between intestinal junction proteins, age-onset dysbiosis, and lifespan determination remains unclear. Here, we show that altered expression of Snakeskin (Ssk), a septate junction-specific protein, can modulate intestinal homeostasis, microbial dynamics, immune activity, and lifespan in Drosophila. Loss of Ssk leads to rapid and reversible intestinal barrier dysfunction, altered gut morphology, dysbiosis, and dramatically reduced lifespan. Remarkably, restoration of Ssk expression in flies showing intestinal barrier dysfunction rescues each of these phenotypes previously linked to aging. Intestinal up-regulation of Ssk protects against microbial translocation following oral infection with pathogenic bacteria. Furthermore, intestinal up-regulation of Ssk improves intestinal barrier function during aging, limits dysbiosis, and extends lifespan. Our findings indicate that intestinal occluding junctions may represent prolongevity targets in mammals.